Cytologic and Functional Alterations of Nasal Mucosa in Smokers: Temporary or Permanent Damage?. (2nd September 2014) - Pagliuca, Giulio; Rosato, Chiara; Martellucci, Salvatore; De Vincentiis, Marco; Fusconi, Massimo; De Virgilio, Armando; Gallo, Andrea
Abstract : Objectives: (1) Quantify the changes in the number of ciliated cells, ciliary beat frequency, and mucociliary transport of the nasal mucosa in smokers. (2) Evaluate if these cytologic and functional changes in smokers are permanent or reversible after smoking cessation. Methods: Ninety healthy volunteers recruited from the staff of A. Fiorini Hospital, Sapienza University of Rome, were enrolled in this study from September 2013 to January 2014. Volunteers were divided into 3 groups (smokers, nonsmokers, and ex‐smokers) composed of 30 subjects each. Cytological features of nasal mucosa and effectiveness of nasal mucociliary clearance were studied focusing on 4 parameters: 1) ratio between the number of ciliated cells and mucous‐secreting cells analyzed through microscopic observation of nasal scraping specimens; 2) in vitro evaluation of ciliary motility; 3) survival time of the ciliated cells analyzed by phase‐contrast microscopy; 4) nasal mucociliary clearance assessed by saccharin transit time test. Results: All parameters are significantly reduced in the group of smokers compared to the nonsmokers ( P <. 05). However, there are no statistically significant differences between the nonsmoker and ex‐smoker groups ( P >. 05). Conclusions: Cigarette smoking causes cytological modifications of nasal mucosa that influence the effectiveness of mucociliary clearance. Our study, although preliminary and conducted on a limited number of cases, suggests that these changes are not permanent and that nasal mucosa of ex‐smokers would recover normal cytologic and functional features.